Synthesis, Characterization and Antibacterial Activities of Some Heterocyclic Compounds from valproic Acid Drug - Ahmed Yousif Rmaidh (Journal of Global Pharma Technology, 2016)
With a view to reducing the acidic effect of valproic acid, its carboxylic group has been recoated to produce 5-membered and 6-membered heterocyclic rings. Heterocyclic derivative as -Thiadiazole, Imidazole, -Oxazine, Quinazoline, Pyrazole and Oxadiazole. Derivatives of valproic acid were prepared by cyclization under different reaction states to produce a good yield. The microbial inhibitory effect of these compounds was assessed in vitro against Gram-positive and Gram-negative bacteria as well as tested against two strains of bacteria (Escherichia coli and Staphylococcus aureus compared with starting material. Compounds (4, 5, 8) showed the highest antibacterial as well as antifungal activities. All compounds have been characterized by IR, 1H NMR and C.H.N analysis.Keywords: Valproic acid, Thiadiazole, Imidazole,-oxazine, Quinazoline, Pyrazole, Oxadiazole, biologically active compounds.